PENGARUH TERPAAN BERITA KEKERASAN APARAT KEPOLISIAN PADA DEMONSTRASI AGUSTUS–SEPTEMBER 2025 DAN TERPAAN TAGAR #POLISIPEMBUNUHRAKYAT DI MEDIA SOSIAL TERHADAP CITRA KEPOLISIAN RI - Rahmania Galuh Pawestri; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This study was motivated by the widespread media coverage of police violence during the August–September 2025 demonstrations, which was followed by public criticism towards the Indonesian National Police, including social media posts using the hashtag #PolisiPembunuhRakyat. Therefore, this study was conducted to examine the impact of exposure to news about police violence during the August–September 2025 demonstrations on the image of the Indonesian National Police and the impact of exposure to the hashtag #PolisiPembunuhRakyat on social media on the image of the Indonesian National Police. This study uses a quantitative approach involving 100 respondents. The data obtained was then analyzed using simple linear regression techniques. The results show that exposure to news reports of police violence during the August–September 2025 demonstrations and exposure to the #PolisiPembunuhRakyat hashtag on social media has a negative influence on the image of the Indonesian National Police. It can be concluded that the higher the level of exposure to news about police violence and the hashtag #PolisiPembunuhRakyat received by the public, the more negative their perception of the Indonesian National Police's image tends to be.